2011
DOI: 10.1073/pnas.1107023108
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor (MIF) exerts antifibrotic effects in experimental liver fibrosis via CD74

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic inflammatory cytokine that has been implicated in various inflammatory diseases. Chronic inflammation is a mainstay of liver fibrosis, a leading cause of morbidity worldwide, but the role of MIF in liver scarring has not yet been elucidated. Here we have uncovered an unexpected antifibrotic role for MIF. Mice genetically deleted in Mif ( Mif −/− ) showed strongly increased fibrosis in two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 49 publications
12
128
3
Order By: Relevance
“…Principally, there is a change from expression of proinflammatory cytokines, chemokines, and profibrotic genes, such as thrombospondin-1 (34), to a profile incorporating genes responsible for scar degradation, such as Mmp12 and Mmp9, genes critical for the clearance of cellular debris, and a number of potential antifibrotic pathways, such as Igf1 (35) and CD74/MIF (33). Furthermore, our data expose the limitations of categorizing macrophage populations from an in vivo setting into the widely used but restrictive M1/M2 paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principally, there is a change from expression of proinflammatory cytokines, chemokines, and profibrotic genes, such as thrombospondin-1 (34), to a profile incorporating genes responsible for scar degradation, such as Mmp12 and Mmp9, genes critical for the clearance of cellular debris, and a number of potential antifibrotic pathways, such as Igf1 (35) and CD74/MIF (33). Furthermore, our data expose the limitations of categorizing macrophage populations from an in vivo setting into the widely used but restrictive M1/M2 paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine (C-X3-C) receptor 1 (CX3CR1)] (32) or antifibrotic effects (e.g. Macrophage migration inhibitory factor (MIF) and CD74) (33) were increased (Fig. 5A).…”
Section: Ly-6c Lo Macrophages Show a Characteristic Gene Expression Pmentioning
confidence: 99%
“…Many studies (Musil et al, 2011) have reported the participation of various cytokines in the chronic viral hepatitis type B disease course; these cytokines, which include MIF, IL-17, and IL-10, elicit a variety of biological functions such as adhesion, phagocytosis, anti-tumor activity, and nitric oxide production and would therefore play important roles in inflammatory responses. The research conducted by Heinrichs et al (2011) revealed an important role for MIF in pathological liver damage; similarly, the results of our preliminary study (Yu et al, 2012) indicated the participation of MIF in the overall occurrence and development of viral hepatitis type B, liver cirrhosis, liver cancer, and other hepatopathies and that changes in the MIF levels were closely related to the extent of liver tissue damage. Miquel et al (2013) reported that immune tolerance was broken following antiviral therapy with Baraclude ® such that the level of MIF in the liver tissue was initially enhanced and then gradually reduced.…”
Section: Baracludementioning
confidence: 49%
“…Other genes driving the transition to M2 responses include Cd74, its ligand Mif, and Sting (TMEM173). CD74, in addition to its role in MHC class II responses, is the receptor for Mif and a soluble truncated form of Cd74 has been found, which binds Mif and neutralizes its proinflammatory effects (Heinrichs et al 2011). The ratio of CD74 to Mif is associated with the development of autoimmune hepatitis in humans (Assis et al 2014).…”
Section: Discussionmentioning
confidence: 99%